Empowerment of Health Cadre in Managing Antenatal Class in Tulikup Village, Gianyar-Bali - Aryastuti, Sri Agung; Ratna Juwita, Dewa Ayu Putu; Cahyawati, Putu Nita; Witari, Ni Putu Diah; Pradnyawati, Luh Gede (Universitas Pendidikan Ganesha, 2020)
Lack of public awareness and knowledge of pregnant women in maintaining their health during pregnancy was one of the problem found in Tulikup Village, Gianyar-Bali. The limited number of health workers in Puskesmas has resulted in the lack of information obtained by the community regarding pregnancy, childbirth and the puerperium. Therefore, cadre empowerment programs as a driving force in managing antenatal classes for pregnant women are expected to overcome these problems. This activity was held in Tulikup Village Hall, and was attended by 6 cadres and 6 pregnant women. The counseling, training and simulation method was used to increase their knowledge and skills about the antenatal class. At the end of the activity, it was found that there was an increase in knowledge regarding the antenatal class. Cadres were able to design an antenatal class, arrange the material that could be given and become a facilitator in activities in it.